Deficiency of GntR Family Regulator MSMEG_5174 Promotes Mycobacterium smegmatis Resistance to Aminoglycosides via Manipulating Purine Metabolism - Deng, Wanyan; Zheng, Zengzhang; Chen, Yi; Yang, Maoyi; Yan, Jun; Li, Wu; Zeng, Jie; Xie, Jianping; Gong, Sitang; Zeng, Huasong (Frontiers in Microbiology, 2022)
The increasing incidence of drug-resistant tuberculosis is still an emergency for global public health and a major obstacle to tuberculosis treatment. Deciphering novel mechanism of mycobacterial antibiotic resistance is crucial for combatting the rapid emergence of drug resistant strains. In this study, we identified an unexpected role of Mycobacterium smegmatis GntR family transcriptional regulator MSMEG_5174 or its homologous gene Rv1152 in Mycobacterium tuberculosis in aminoglycoside antibiotics resistance via manipulating purine metabolism. Deficiency of MSMEG_5174 rendered Mycobacterium smegmatis highly resistant to aminoglycoside antibiotics treatment. Heterogenous expression of Rv1152 in MSMEG_5174 mutants restored antibiotics-induced bacterial killing. Combination transcriptome with metabolome profiling revealed MSMEG_5174 negatively regulates the expression of genes associated with purine metabolism and metabolites accumulation. Moreover, ectopic expression of one dysregulated gene xanthine dehydrogenase MSMEG_0871 in Mycobacterium smegmatis, or Mycobacterium smegmatis cultured with purine metabolites xanthine elicited significant decreased in aminoglycoside antibiotics lethality. Together, our finding revealed a role of MSMEG_5174 in controlling purine metabolism and antibiotic resistance.